COMPARATIVE ANALYSIS OF STATIC AND DYNAMIC MOE OF PANNÓNIA POPLAR TIMBER FROM DIFFERENT PLANTATIONS - Kánnár Antal (WOOD RESEARCH, 2021)
The aim of this study has been to investigate the suitability of Pannónia poplar (Populus × euramericana cv. Pannónia) timber for structural purposes. Static and dynamic modulus of elasticity (MOE) has been determined on samples of 4 different Hungarian plantation origins. The results of the dynamic test showed the same range as the static test, showing a good correlation of the two measurements. As result it can be stated that the domestic Hungarian Pannónia poplar species have in average 11000 N.mm-2 modulus of elasticity. This exceeds considerably the threshold limit value (7000 N.mm-2) necessary for structural applications according to Eurocode 5. Therefore Pannonia poplar is suitable for structural applications, and are a good alternative of the widely used coniferous species in construction sector.